Revisão bibliográfica sobre efeitos de raças e heterose no desempenho de bovinos de corte em confinamento - (:unkn) unknown (Universidade Federal do Pampa, 2010)
The feedlot beef cattle deals in small areas, the concentration of a large number of animals, given the fullness of their food needs, allowing all to express their genetic potential, especially of the characteristics related to weight gain. It is most commonly used for finishing cattle, which is the stage of production before slaughter the animal. The present work aims at obtaining research data and analyzes the results of experiments, verifying the performance of different genotypes (Bostaurus and Bosindicus) and their reciprocal crosses (heterosis), subjected to confinement system, evaluating consumption of raw dry, weight gain and feed conversion during the finishing phase of these individuals.In the studies analyzed, genotypes that performed better in the confinement system, with better feed conversion and average daily gain in weight, were the descendants of heterosis between breeds Charolais and Nellore, with the blood level of 5 / 8 Nellore 3 / 8 Charolais.
Keywords: Confinamento; Bovinos de corte; Índice de conversão alimentar; Ganho médio diário de peso; Confinement; Beef cattle; Feed conversion rate; Average daily weight gain; CNPQ::CIENCIAS AGRARIAS